Extended-Release Fluvastatin is Associated with Improved Cardiac Outcomes after Elective Major Vascular Surgery: Results from DECREASE III - Vinall, Maria (MD Conference Express, 2008)
Results of the Dutch Echographic Cardiac Risk Evaluation Applying Stress Echo III [DECREASE III; ISRCTN83738615] study showed that extended-release fluvastatin therapy in addition to beta-blockers is associated with significantly improved perioperative cardiac outcomes in statin-naïve high-risk patients who undergo elective vascular surgery.